Toxoplasma Reduces Complications of Parkinson’s Disease: An Experimental Study in BALB/c Mice - Mohammad Nohtani; Qasem Asgari; Fattaneh Mikaeili; Vahid Reza Ostovan; Mehdi Mirzaeipour; Mohammad Saleh Bahreini; Sajad Rashidi (Journal of Parasitology Research)
Background. Parkinson’s disease (PD) has been described in dopamine brain level reductions. Conversely, several studies have shown that Toxoplasma parasite can increase the level of dopamine in an infected host. This study was conducted to assess the serum, cerebral dopamine levels, and downregulation of Parkinson’s disease manifestations in mice with chronic toxoplasmosis. Methods. PD induction was done by oral inoculation of rotenone into BALB/c mice. To induce the chronic infection, cysts of T. gondii Prugniaud strain (genotype II) were injected intraperitoneally into the mice. The rotarod test was used for the evaluation of functional motor disorders in experimental mice. The serum and cerebral dopamine levels of the mice were also measured by using high-performance liquid chromatography (HPLC) on consecutive periods (10 days). Results. Findings of the rotarod test showed the highest and lowest average of running duration belonged to the uninfected mice and PD mice, respectively. Remarkably, the running duration of infected mice with PD was higher than PD mice. As well, the level of serum and cerebral dopamine increased in mice with PD and toxoplasmosis in comparison with PD mice. Conclusion. Increasing the serum and cerebral dopamine levels in mice infected with toxoplasmosis is related to the presence of the parasite. Moreover, the dopamine upregulation due to the infection is effective in the reduction of PD complications.